Predatory Conferences are Cybercrimes: Be Careful What You Sign up for! - Sue Turale (Pacific Rim International Journal of Nursing Research, 2023)
Today, there are many scams on the internet, including predatory publishing, predatory journals and predatory conferences. These fraudulent activities are a form of cybercrime and cause reputational damage to science and scientists in many disciplines. These activities also threaten the integrity of modern health care and scholarship. In this paper, the scamming associated with predatory conferences is discussed. An email is the most typical way researchers are asked to sign up for a predatory conference. Nurses, midwives and others are warned of the potential for lost funds, time, effort and emotional investment if they invest in a non-existent conference or one of low quality. Vigilance is needed by experienced scholars and clinicians, as well as early career researchers and graduate students, to try to detect when conferences are not what they seem. Suggestions are given here to try to determine if the conference is predatory. Understanding the extent of predatory conferences and evidencing clear strategies to reduce the likelihood of being scammed are much needed. While many papers are published about this problem, there is a lack of research, and this is an opportunity for nurses and midwives to consider for their next project. Action is clearly needed to reduce or eliminate these scams, and individuals and groups affected by predatory conferences need to report this to their institutions who must refer the matter to law enforcement agencies.